2016
DOI: 10.1093/europace/euv419
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after cryoablation vs. radiofrequency in patients with paroxysmal atrial fibrillation: impact of pulmonary veins anatomy

Abstract: Our findings suggest that mid-term outcomes of cryoballoon ablation for paroxysmal AF ablation are similar to those of radiofrequency, regardless of PV anatomy. The presence of anatomical variants of PVs should not discourage the referral of patients with paroxysmal AF for cryoballoon ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 19 publications
6
55
0
4
Order By: Relevance
“…These study results are consistent with the outcomes reported in other global trials of the effectiveness of cryoballoon. [8][9][10][11][12] Although this study was a PMS, the safety outcome seems not a significant problem with new cryoballoon users.…”
Section: Conflicts Of Interestmentioning
confidence: 89%
See 2 more Smart Citations
“…These study results are consistent with the outcomes reported in other global trials of the effectiveness of cryoballoon. [8][9][10][11][12] Although this study was a PMS, the safety outcome seems not a significant problem with new cryoballoon users.…”
Section: Conflicts Of Interestmentioning
confidence: 89%
“…Most of the studies demonstrated a similar efficacy between cryoablation and irrigated-tip RF ablation for paroxysmal AF. [8][9][10][11][12] In most studies, procedural duration was shorter and fluoroscopic exposure a little longer than with conventional RF ablation with 3D mapping system. Nevertheless, efficacy is not the only issue we need to consider; safety is also paramount before making this ablation technique available to most operators, including less experienced doctors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that the size and shape of the balloon are predefined, PV anatomy, including number of veins, presence of common trunk, angulation, ostium area and ovality, may have an impact on CB ablation efficacy. A few studies which addressed this issue provided inconsistent results [2][3][4][5][6] . Therefore, the aim of our study was to examine whether PV ostia anatomy is related to the acute and long-term effects of CB of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Wybór techniki ablacyjnej powinien zatem być oparty na lokalnej dostępności danej metody, analizie kosztów procedury, jak również preferencjach oraz doświadczeniu danego ośrodka w konkretnej technice ablacji AF. Krótsza krzywa uczenia i bardziej jednorodne wyniki niezależnie od indywidualnej anatomii ujść żył płucnych [8], jak również mniejsza pracochłonność zabiegu stanowią silne strony techniki krioablacyjnej.…”
unclassified